Computational fluid dynamics applied to the ventilation of small-animal laboratory cages. (April 2021) - Katz, Ira; Voronetska, Kateryna; Libardi, Mickaël; Chalopin, Matthieu; Privat, Patricia; J Esdaile, David; Mougin, Guillaume; Farjot, Géraldine; Milet, Aude
Several studies based on in vivo or in vitro models have found promising results for the noble gas argon in neuroprotection against ischaemic pathologies. The development of argon as a medicinal product includes the requirement for toxicity testing through non-clinical studies. The long exposure period of animals (rats) during several days results in technical and logistic challenges related to the gas administration. In particular, a minimum of 10 air changes per hour (ACH) to maintain animal welfare results in extremely large volumes of experimental gas required if the gas is not recirculated. The difficulty with handling the many cylinders prompted the development of such a recirculation-based design. To distribute the recirculating gas to individually ventilated cages and monitor them properly was deemed more difficult than constructing a single large enclosure that will hold several open cages. To address these concerns, a computational fluid dynamics (CFD) analysis of the preliminary design was performed. A purpose-made exposure chamber was designed based on the CFD simulations. Comparisons of the simulation results to measurements of gas concentration at two cage positions while filling show that the CFD results compare well to these limited experiments. Thus, we believe that the CFD results are representative of the gas distribution throughout the enclosure. The CFD shows that the design provides better gas distribution (i.e. a higher effective air change rate) than predicted by 10 ACH.